EFFECTIVENESS OF THE DEATH PENALTY IN REDUCING CRIME RATES IN INDONESIA: CASE STUDY OF NARCOTICS CRIME - Achmad Yusuf (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research aims to analyze the effectiveness of the death penalty in reducing the number of narcotics crimes in Indonesia. The approach used is juridical-normative and empirical, by examining secondary data from legal documents and narcotics crime statistics, as well as primary data through interviews with legal experts and law enforcement officials. The analysis was carried out descriptively qualitatively to evaluate the impact of the death penalty on trends in narcotics crimes as well as other factors that influence the increase or decrease in narcotics cases. The research results show that even though the death penalty is applied to narcotics crime perpetrators, the number of narcotics cases has continued to increase in recent years. Other factors such as weak law enforcement, the continuity of narcotics networks, and the socio-economic conditions of perpetrators also contribute to the high crime rate. In addition, the implementation of the death penalty in Indonesia faces various legal, social and political obstacles, and has received criticism from the international community. Thus, this research concludes that the death penalty has not been proven effective as the main instrument in eradicating narcotics crimes. Therefore, a more comprehensive approach is needed, such as strengthening the legal system, rehabilitation-based prevention strategies, and international cooperation in fighting narcotics networks more effectively and sustainably.